REPRESENTASI FEMINISME DALAM FILM 7 HATI, 7s CINTA, 7 WANITA - Pratiwi, Ayu Pramitria; Amanda Gelgel, Ni Made Ras Amanda Gelgel; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2018)
ABSTRACT w             Film discusses societal themes or phenomena and represents reality. It also speaks about the role of women in the media, who focuses on the struggle to withstand the gender equality for all of the women in the world. This contains ramework of liberal and socialist feminism in struggling for society problem which focuses on the equal opportunity and also right for every individual, particularly women that is being represented in movie entitled 7 Hati, 7 Cinta, 7 Wanita. It represents the phenomenon through the drama-genre movie. This research aimed to find out in-depth the values of feminism which represented in a movie entitled 7 Hati, 7 Cinta, 7 Wanita. This particular research was conducted using semiotic analysis method proposed by Charles Sanders Pierce through the Triangle Meaning concept by qualitative research and constructivist paradigm. The result of this study was 7 Hati, 7 Cinta, 7 Wanita is an Indonesian film that contains all the values of liberal and socialist feminism and being represented through 6 categories which contained in some scenes in this movie.   . Keywords: feminism, movie, 7 Hati 7 Cinta 7 Wanita, semiotics